AGRICULTURAL MECHANISATION: ACHIEVEMENTS, IMPACTS AND FUTURE PROSPECTS - Samadov Muhiddin Akhadovich (Western European Studies, 2024)
Agricultural mechanization has revolutionized the way farming is done around the world, increasing efficiency, productivity and sustainability in agricultural practices. This scientific article provides extensive information on the evolution of agricultural mechanization, its impact on farming systems, environmental sustainability, and rural living conditions. By exploring the current trends, challenges and future prospects of agricultural mechanization, this article highlights the transformative role of technology in shaping the future of agriculture.
Keywords: transformative; prospects; mechanization; highlights